FUSÕES E AQUISIÇÕES: UMA EXPERIÊNCIA DE INTEGRAÇÃO COM SUCESSO - Moraes, Carlos Roberto Menezes de (2008)
This essay contributes to the discussion of merger and acquisition as processes. It explores the relationship between the motivation for the purchase and integration strategy. As object of the research, we selected SmithKline, a global company. The results indicate that one of challenges to these operations in Brazil is the adequate development of the stages of the process. The key rationale behind acquisitions is to increase shareholder value through the combination of two organizations. Value from acquisitions is mainly realized through the exploitation of economies of scale and scope, the realization of synergies, and access to new technologies and capabilities. The common factor underlying these sources of value creation is the transfer of knowledge Nonetheless, the transfer and utilization of knowledge through acquisitions is contingent on the successful integration of the acquired unit. The integration not only needs be successful at the operational procedural level, but also at the human level: the employees need to share the same organization context and identify in order to develop a cooperative relationship. However, it is precisely in the integration process where most merger and acquisition failures can be found. Differences in organization culture and processes, managerial systems and communication styles are substantial obstacles on the way to integration. In this essay, we address an often neglected positive side of acquisitions: if integrated correctly, acquisitions may play an essential role in the organizational knowledge creation and multiplication process. The challenges related to the integration of the two joining organizations are addressed. Main obstacles to successful integration are presented and described. Several recommendations are presented on how to overcome the various obstacles related to integration. Finally, we summarize this essay and derive a few fundamental conclusions. However, news surveys are suggested using new knowledge sources in order to find new innovative strategies that ensure the firm s future success.(AU)